"More than a Job, it's a Purpose": A Psychology of Working Perspective of the Working Experiences for Individuals with Intellectual and Developmental Disabilities. (May 2022) - Gilson, Carly B.; Sinclair, James; Whirley, Mary L.; Li, Yi-Fan; Blustein, David L.
Adults with intellectual and developmental disabilities (IDD) aspire to work, though they are often excluded from the workforce. However, little is known about the perspectives and work experiences of adults with IDD viewed through a vocational psychology lens. Our study focused on the Psychology of Working theoretical (PWT) framework, which is anchored in inclusivity, lived experiences, and equity. We conducted semi-structured interviews with 18 adults with IDD across the United States to understand how they make meaning of work and the extent to which their lived experiences aligned with the PWT taxonomy. We employed consensual qualitative research to analyze participants' views within the three functions of the PWT taxonomy (i.e., power and survival, social connection, and self-determination). Our findings affirm the taxonomy as an appropriate framework to apply to the working experiences of adults with IDD. We discuss implications of this study for research and practice in vocational psychology.